Upaya Meningkatkan Kemampuan Komunikasi Matematis dan Self Regulated Learning Siswa Melalui Penerapan Model Pembelajaran Reflektif - Oktafianto, Arif (Cartesian: Jurnal Pendidikan Matematika, 2024)
This research aims to improve students' mathematical communication and self-regulated learning skills through the application of the reflective learning model. The method used in this research is classroom action research at a class IX private junior high school in South Tangerang with a qualitative research approach. Data collection techniques are tests in the form of story questions and questionnaires. The research results show a gradual increase in mathematical communication skills from the implementation of the reflective learning model. Judging from the average score of the end-of-cycle test results, students' abilities increased to 78 in cycle II. When compared with the average value of the final test in cycle I of 61. This increase has reached the predetermined indicator of success in action, namely 75. Students' self-regulated learning increased in cycle II, when compared with cycle I. Descriptively, this result is proven by Students' explanations of answers are increasingly developing, they are able to write down what they know and are asked, create pictures/visuals from story problem situations, write mathematical models and solve them in a systematic way. Students' attitudes appear enthusiastic in learning, more independent and more active in asking and answering questions.